Adapting Islamic Legal Sources to Contemporary Challenges: The Role of Ijtihad and Fatwa in Modern Muslim Societies - Wardhani, Ayu Era; Rahmawati, Rahmawati; Badriya, Nurul (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2025)
Classical Islamic legal sources — the Qur'an, Hadith, ijma', and qiyas — were codified in historical contexts vastly different from the realities confronting contemporary Muslim societies navigating technological disruption, globalization, and rapid social transformation. While these sources retain their foundational normative authority, their direct application to unprecedented modern challenges remains methodologically constrained, generating a persistent gap between classical legal tradition and contemporary Muslim life. This study aims to analyze the relevance of classical Islamic legal sources in modern Muslim societies and to construct an integrated framework positioning ijtihad and fatwa as complementary adaptive instruments for bridging this gap. Employing systematic library research, data were collected from classical jurisprudential texts and peer-reviewed contemporary scholarship, and analyzed through content analysis, thematic synthesis, and critical interpretation. The findings reveal that Islamic law's adaptive capacity is intrinsic to the tradition itself, and that ijtihad and fatwa function most effectively not as independent mechanisms but as sequential and mutually dependent stages within a coherent process of legal adaptation. The study concludes that strengthening collective ijtihad, enhancing inter-institutional fatwa coordination, and reconceiving Islamic legal education are essential prerequisites for ensuring Islamic law's continued relevance in an increasingly complex contemporary world.